Modern challenges and prospects for the development of BIM-modeling in Russia in the age of digitalization - N. V. Vozgoment (State University of Management, 2020)
The article analyses the general problems of implementing BIM technologies in the construction industry of the Russian Federation. The paper determines the influence of the concept of scientific and technological progress on the development of information modeling in construction. The author reflects the concept of BIM modeling in the economic sphere. The study considers the stages of implementation and problems of adoption of innovative technologies in construction. The author suggests ways out of the current practice of organizing mutual relations between participants in the construction process.The article considers the fundamental and key aspects of the processes of domestic development of information design programs in the construction sector and in the Russian economy as a whole. The paper reflects the influence of foreign initiative and foreign funding in the functionality of information design software utilities. The study reflects the impact of the introduction of information BIM technologies in the construction processes at various stages of the investment project development: from development and design to commissioning, subsequent use and, if necessary, demolition of the object. The author presents arguments that justify the need to develop BIM modeling in the construction processes in Russia.The paper gives a modern interpretation of the concept of information modeling in construction on the territory of the Russian Federation. The author supposes that it is not necessary to introduce information BIM modeling in Russia at all acceptable scales (volumes) of its technological development abroad. The article presents the main activities that contribute to the development of progress in the implementation of BIM technologies on the territory of Russia in the construction sector and in general in the domestic business. The study considers and systematizes the goals and objectives of digitalization of the economy, including in construction. The paper discusses design functions in construction, promising variations of improving the quality of construction projects and reducing the level of risks and costs of the project.